Fontainebleau engraving by William Miller after Turner R538 - William Miller (Wikimedia Commons, 1836)
Notice iconographique issue de Wikimedia Commons. Titre: Fontainebleau engraving by William Miller after Turner R538. Fontainebleau (Rawlinson 538) engraving by William Miller after Turner, published in The Miscellaneous Prose Works of Sir Walter Scott, Bart. Embellished with Portraits, Frontispieces, Vignette Titles and Maps. The Designs of the Landscapes from Real Scenes by J.M.W. Turner, R.A.. Edinburgh: Robert Cadell, Edinburgh | Whitaker, Arnot, and Company, London | John Cumming, Dublin 1834 - 1836
Droits : Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; Patrimoine; Wikimedia Commons; Iconographie